A novel digital competence assessment tool for parents: Development and validation study - Yitong Jia; Bojun Xu; Yuxuan Li; Xinqi Zhuang; Jianzhong Zhang; Yin-Ping Zhang (Digital Health)
Background In the digital era, parental digital competence is being recognized to be essential for effective parenting and improved child health. To address a gap in existing tools that lack specificity for assessing digital competence within the childcare context, this study aimed to develop and validate a novel Parental Digital Competence Scale (PDCS). Methods The PDCS was developed through a four-phase process: (1) Clarifying the content to be measured based on the European Commission's Digital Competence Framework; (2) Creating an item pool through a literature review; (3) Refining items with expert panel feedback and a pilot test; and (4) Conducting a psychometric validation to evaluate item characteristics. The validation study included 477 family caregivers selected from Northwest China. Construct validity with exploratory (EFA, n  = 248) and confirmatory factor analysis (CFA, n  = 229) was carried out to identify the factor structure of the scale. Convergent and discriminant validity were evaluated. The reliability was assessed through internal consistency, split-half reliability, and test–retest reliability. Results Twenty-three items were included in the final instrument. The content validity index of the PDCS reached 0.975. The EFA results revealed a three-factor structure that explained 80.499% of the total variance. The CFA results further demonstrated that the second-order three-factor model achieved a satisfactory fit. The final version of PDCS included three dimensions: Digital Methods Application, assessing parents’ skills in leveraging digital tools for information creation, problem-solving, and communication; Digital Security, covering online safety, privacy protection, and responsible digital behaviors; and Information Retrieval and Evaluation, measuring parental ability to locate, understand, and critically appraise online child-related information. The PDCS demonstrated high internal consistency (Cronbach's α  = 0.981). Conclusions The PDCS seems to be a valid and reliable tool. Its potential application enables researchers to identify parental digital competence gaps, track improvements following targeted interventions and promote safer, more productive digital family environments.